Pirates, ports, and coasts in Asia historical and contemporary perspectives - Kleinen, John; Osseweijer, Manon (IIAS/ISEAS series on maritime issues and piracy in Asia, 2010)
Pirates, Ports, and Coasts in Asia aims to fill some of the hostorical gaps in the coverage of maritime piracy and armed robbery in Asia. The authors highlight a variety of activities ranging from raiding, destroying and pillaging coastal villages and capturing inhabitants to attacking and taking over vessels, robbing and then trading the cargo and its people. Generally speaking, what connects these activities is the fact that they are carried out at sea, often in the coastal inshore waters, by vessels attacking other vessels or raiding coastal settlements. Acts of maritime piracy cannot be regarded as being located outside the relevant framework of the coastal zone. Coastal zones have therefore become highly desirable places subject to great social and ecological pressures. Piracy being the most dramatic of marginal(ized) maritime livelihood, this book brings the relationship between pirates, ports, and coastal hinterlands into focus.